Lolium perenne peptide immunotherapy is well tolerated and elicits a protective B‐cell response in seasonal allergic rhinitis patients. Issue 6 (13th February 2018) - Mösges, R.; Koch, A. F.; Raskopf, E.; Singh, J.; Shah‐Hosseini, K.; Astvatsatourov, A.; Hauswald, B.; Yarin, Y.; Corazza, F.; Haazen, L.; Pirotton, S.; Allekotte, S.; et al.
Abstract: Background: Systemic allergic reactions are a risk for allergen immunotherapy that utilizes intact allergen preparations. We evaluated the safety, efficacy and immune mechanisms of short‐course treatment with adjuvant‐free Lolium perenne peptides (LPP) following a 6‐week dose‐escalation protocol. Methods: In a prospective, dose‐escalation study, 61 grass pollen–allergic patients received 2 subcutaneous injections of LPP once weekly for 6 weeks. Safety was assessed evaluating local reactions, systemic reactions and adverse events. The clinical effect of LPP was determined by reactivity to the conjunctival provocation test (CPT). Specific IgE, IgG4 and blocking antibodies were measured at baseline (V1), during (V6) and after treatment (V8). Results: No fatality, serious adverse event or epinephrine use was reported. Mean wheal diameters after injections were <0.6 cm and mean redness diameters <2.5 cm, independent of dose. Transient and mostly mild adverse events were reported in 33 patients. Two patients experienced a grade I and 4 patients a grade II reaction (AWMF classification). At V8, 69.8% of patients became nonreactive to CPT. sIgG4 levels were higher at V6 (8.1‐fold, P  <   .001) and V8 (12.2‐fold, P  <   .001) than at V1. The sIgE:sIgG4 ratio decreased at V6 (−54.6%, P  <   .001) and V8 (−71.6%, P  <   .001) compared to V1. The absolute decrease in IgE‐facilitated allergen binding was 18% ( P  <   .001) at V6 and 25% ( P  <   .001) at V8. Conclusion: Increasing doses of subcutaneous LPP appeared safe, substantially diminished reactivity to CPT and induced blocking antibodies as early as 4 weeks after treatment initiation. The benefit/risk balance of LPP immunotherapy remains to be further evaluated in large studies.